Optic disc vasculitis secondary to mononucleosis: a case report - N. A. Voroshilova; M. K. Lukina (Российский офтальмологический журнал, 2024)
Vasculitis of the retina and the optic nerve is one of the most complex, rare and challenging issues in clinical ophthalmology. Managing patients with this diagnosis is difficult because practical ophthalmologists lack sufficient experience, clinical manifestations and courses of the disease are versatile and technical means of full-scale diagnostics and observation, including fluorescein angiography are limited. The report illustrates a particular case of optic nerve vasculitis in a young female patient. We assumed that an infectious mononucleosis that she had experienced led to immune dysfunction and the development of autoimmune vasculitis of the optic nerve. An immunosuppressive therapy was prescribed, which allowed achieving a good clinical result.